2013
DOI: 10.1371/journal.pone.0080305
|View full text |Cite
|
Sign up to set email alerts
|

STX140, but Not Paclitaxel, Inhibits Mammary Tumour Initiation and Progression in C3(1)/SV40 T/t-Antigen Transgenic Mice

Abstract: Despite paclitxael's clinical success, treating hormone-refractory breast cancer remains challenging. Paclitaxel has a poor pharmacological profile, characterized by a low therapeutic index (TIX) caused by severe dose limiting toxicities, such as neutropenia and peripheral neuropathy. Consequently, new drugs are urgently required. STX140, a compound previously shown to have excellent efficacy against many tumors, is here compared to paclitaxel in three translational in vivo breast cancer models, a rat model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Interestingly, STX140 did not affect cell viability in a non-tumorigenic human breast cell line [154]. This compound also inhibited initiation and progression of mammary tumors in adult mice [155] suggesting that STX140 is a promissory 2ME 2 analog that can be potentially used in human breast cancer.…”
Section: Stx140 (2-methoxyestradiol-317-oo-bissulphamate)mentioning
confidence: 99%
“…Interestingly, STX140 did not affect cell viability in a non-tumorigenic human breast cell line [154]. This compound also inhibited initiation and progression of mammary tumors in adult mice [155] suggesting that STX140 is a promissory 2ME 2 analog that can be potentially used in human breast cancer.…”
Section: Stx140 (2-methoxyestradiol-317-oo-bissulphamate)mentioning
confidence: 99%
“…Furthermore, favourable pharmacokinetic properties of STX140, including good bioavailability and low metabolism in rodents 105 , have proved its major clinical advantages 106 also for chemotherapy-resistant tumours 107 . In 2013, in vivo studies with three breast cancer models 108 demonstrated that STX140 had greater anticancer efficacy and therapeutic index as well as reduced neurotoxicity compared to paclitaxel (clinically used for hormone-refractory breast cancer), which may bring significant benefits to patients with breast cancer. Furthermore, a 2-[ 11 C]methoxy derivative of STX140 has been reported as a new potential imaging agent of STS in tumours in the positron emission tomography technique 109 .…”
Section: Multitargeting Agents With Sts Inhibitory Activitiesmentioning
confidence: 99%
“…Moreover, β3-tubulin overexpression has also been reported to confer resistance to paclitaxel and vinorelbine, but with no effect to the resistance to colchicine-site binding agents [ 25 ]. Lastly, STX140, but not paclitaxel, inhibits mammary tumour initiation and progression in transgenic mice [ 26 ].…”
Section: Introductionmentioning
confidence: 99%